Quantifying the influence of optical coherence tomography beam tilt in each retinal layer - David Bissig; Shasha Gao; Haohua Qian (PLoS ONE, 2025)
Purpose Well-aligned microstructures within the retina – like retinal nerve fiber layer (RNFL) axons – differentially reflect light depending on its angle. Our goal was to quantify the influence of optical coherence tomography (OCT) beam tilt on reflectivity of each layer of the mouse retina. Methods We collected OCT images in a single plane capturing the optic nerve head, temporal retina, and nasal retina, while tilting the OCT beam at various angles. We converted signal intensities to estimated attenuation coefficients (eAC). The attenuation coefficient describes how quickly the remainder of an OCT beam’s light is absorbed or scattered at a given depth into the retina. A single-ellipse model based on prior literature was calculated at each retinal depth, describing the maximum eAC across all tilts (ellipse semi-major axis), the beam tilt eliciting that maximum eAC, and eAC’s dependence on beam tilt (semi-major versus semi-minor axes). Post hoc, the inner retina bore an unexpectedly complex relationship between beam tilt and eAC, which we explored with a two-ellipse model. Results eACs in the temporal and nasal retina were dissimilar at specific beam tilts, but this was near-completely explained by differences in microstructure alignment. Dependence on beam tilt was substantial over the photoreceptors, but non-zero in all retinal layers. Post-hoc, two-ellipse models implied that microstructures vitread to the external limiting membrane were well-aligned with the photoreceptor inner and outer segments, and a small fraction (≥0.3%) of that tissue is especially translucent. Conclusion We mapped microstructure alignment throughout the retina. Expected findings at the photoreceptor inner and outer segments are complemented by new evidence of unusually translucent microstructures spanning much of the retina, possibly representing Müller glia.